2021
DOI: 10.3390/agronomy11010119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cover Crops and Poultry Litter on Selected Soil Properties and Yield in Dryland Soybean Production

Abstract: Soil biological properties are important for the stabilization and preservation of a good soil structure. Management practices can affect the diversity and population of microorganisms, which could beneficially change soil properties and promote a more sustainable dryland crop production. This study was established near Pontotoc, MS, USA (34°07′ N, 88°59′ W) on an Atwood silt loam (fine-silty, mixed, semiactive, thermic Typic Paleudalf) to evaluate the impacts of cover crops, planting dates and fertilizer sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 88 publications
(110 reference statements)
2
11
0
Order By: Relevance
“…Soil samples used for measurement of physical and chemical properties were stored at −20 • C and subsamples used for DNA analysis were stored at −80 • C (in 50 mL tubes). Detailed protocols were described in one of our previous studies [28]. Particle size [38], total C and N [39], soil pH [40], water-stable aggregates (WSA) [41], easily extractable glomalin-related soil proteins (EE-GRSP) [42], and permanganate oxidizable C (POXC) [43] were measured on air-dried samples, which were ground to pass a 2-mm sieve.…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil samples used for measurement of physical and chemical properties were stored at −20 • C and subsamples used for DNA analysis were stored at −80 • C (in 50 mL tubes). Detailed protocols were described in one of our previous studies [28]. Particle size [38], total C and N [39], soil pH [40], water-stable aggregates (WSA) [41], easily extractable glomalin-related soil proteins (EE-GRSP) [42], and permanganate oxidizable C (POXC) [43] were measured on air-dried samples, which were ground to pass a 2-mm sieve.…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
“…Importantly, no-till and cover crops enhance soil microbial growth and activity [24,25]. Organic soil amendments, such as poultry litter, a soil health practice which when combined with tillage and cover crop conservation practices are agronomically beneficial and promote soil health [26][27][28]. Even in soybeans, which fix their own nitrogen, poultry litter improves organic carbon, which influence the soil health and increases soybean yields [28,29], where application time and rate are critical.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean production is affected by soil fertility and soil water content in relation to the soil tillage system [26][27][28], and the quality of soybean production is affected more by fertilization and climatic factors [29].…”
Section: Introductionmentioning
confidence: 99%
“…Gattullo et al [9] assessed the effect of a fescue cover crop on soil quality, yield, and grape qualitative parameters and reported that cover crops increased, on average, soil organic carbon, total N, other soil chemical properties. Pokhrel et al [10] evaluated the impact of cover crops and poultry litter on selected soil chemical properties and yield in dryland soybean production system and found no significant effects of cover crops over the short period of the study.…”
Section: Introductionmentioning
confidence: 99%